Forensic Linguistic Profiling of Defendant 'DRL' in the Helwa Beautycare Case - Anzlina, Nur; Zuxi, Liu; Suswandi, Irwan; Yusra Zahirah Zahra, Tsurayya (Universitas Ahmad Dahlan, 2025)
Linguistic profile analysis was used to analyze the dialect, idiolect, register, and language variation of the defendant